Analysis of Figurative Language in “Rewrite the Stars” Song Lyrics - Erni Putri Suriyani Bawemenewi; Ni Wayan Swarniti (CV. Tirta Pustaka Press, 2024)
It is important to analyze the use of figurative language in song lyrics. That is why the researcher wants to examine figurative language more thoroughly, especially in the song